Phylogenetic placements of the barbin genera Discherodontus, Chagunius, and Hypselobarbus in the subfamily Cyprininae (Teleostei: Cypriniformes) and their relationships with other barbins - Yang, Lei; Hirt, M. Vincent; Sado, Tetsuya; Arunachalam, M.; Manickam, Raja; Tang, Kevin L.; Simons, Andrew M.; Wu, Hsin-Hui; Mayden, Richard L.; Miya, Masaki (Zootaxa, 2012)
The barbin genera Discherodontus Rainboth 1989, Chagunius Smith 1938 and Hypselobarbus Bleeker 1860 are distrib-uted in Southeast and South Asia and are among the least studied taxa of the order Cypriniformes. Few morphologicalstudies have been conducted on these genera and only a very limited number of morphological characters were employedto hypothesize or infer their monophyly, inter-relationships, and relationships with other barbins. The main aim of thisstudy is to examine the monophyly of these three genera and propose hypothesis of relationship among these taxa andother barbins based on a molecular phylogeny of the subfamily Cyprininae. A total of 106 cypriniform species were sam-pled, including 64 species and 31 genera of barbins collected from Eurasia and Africa. Partitioned maximum likelihoodanalysis was performed using DNA sequences derived from five mitochondrial genes (5601 bp): cytochrome c oxidasesubunit I (COI), cytochrome b (Cyt b), 16S ribosomal RNA (16S), NADH dehydrogenase subunits 4 (ND4) and subunits5 (ND5). The resulting phylogeny demonstrates that, under current taxon sampling, Discherodontus, Chagunius, andHypselobarbus are all monophyletic genera. Together they do not form a monophyletic group, as hypothesized in previousstudies, but are instead part of three distinct and unrelated clades. Discherodontus constitutes the basal lineage of a cladeformed by Southeast Asian barbins (e.g. Poropuntius, Hypsibarbus, Balantiocheilos); Chagunius is basal to a cladeformed mainly by Puntius and allies (although this relationship was only weakly supported); Hypselobarbus and Barbuscarnaticus formed a clade sister to a clade including Tor, Neolissochilus, Labeobarbus, and Varicorhinus. Homoplasy andshared plesiomorphy of some hypothesized important morphological characters employed in previous studies that led researchers to hypothesize earlier relationships are discussed.